Quality Experience: Co-Creation and Excellent Service Juragan 99 Trans Bus Land Transportation Services With Currency Moderation - Syarifah Munawaroh; Surya Bintarti; Taufiq Rachman; Joni Heruwanto; Muh. Ali Maskuri (Journal Research of Social Science, Economics, and Management, 2024)
Transportation can never be separated from one's daily life, such as going to school, office, market or other distant places. Transportation is divided into three namely, land, sea and air transportation. In Indonesia, land transportation is more widely used than air and sea transportation. Land transportation such as buses, private cars and trains. Bus is a means of land transportation that is ranked third most often used. This study aims to test product variations (co-creation) and service quality (service excellent) against the quality of experience (quality experience) with price (currency) as moderation. The number of respondents in this study was 108 respondents who had used Juragan 99 Trans Bus transportation services in the Bekasi Regency area. This population collection is non-probality sampling and the respondent retrieval technique is purposive sampling. This research was processed using regression techniques, where the processing used SmartPLS 3 software. This research proves 1) The variety of products (co-creation) offered by the Juragan 99 Trans Bus has an effect on the high quality of experience. 2) The quality of service (service excellent) offered by the Juragan 99 Trans Bus influences the high quality of experience (quality experience). 3) Product variations (co-creation) which are moderated by price (currency) influence the high quality of experience. 4) Quality of service (service excellent) which is moderated by price (currency) influences the high quality of experience (quality experience).